Moving from talk to action: A commitment to ensuring equity must ground our efforts to transform the human experience - Jason Wolf (The Beryl Institute, 2021)
When we first introduced the call for submissions for this special issue last August, we were still churning in the first wave of the COVID pandemic. Just three to four months from the start of an unending rash of unexpected and harsh realities that we were faced with in healthcare and in society at large, we too found that the moment was revealing all the weaknesses and wounds that had existed in the foundations of the healthcare system from well before the pandemic hit. Our own research at The Beryl Institute in 2020 reinforced a quiet reality: that people do experience discrimination in healthcare. In fact, 35% of Black Americans reported experiencing some sort of discrimination often or sometimes,1 and this unquestionably has an impact on their care. The challenges that healthcare has long faced in ensuring equitable access, care, treatment and outcomes were only further laid bare by the crisis. And there is still much work to do. The road that led to this Special Issue reveal that truth and the articles shared on these pages confirm it. But they too show us seeds of possibility, that when we focus on what is right for all who healthcare aspires to serve, then we can truly achieve the greatest in human experience for all. And that is exactly what every person ultimately deserves.